Resilience of Anchovy Fishermen (Pa'perre-Perre) in Maccini Sombala Village, North Galesong District, Takalar Regency - Shofi Dzakwani; Firman Firman; M. Chasyim Hasani; Mardiana E. Fachry; Abdul Wahid; M. Irham Ilyas; Alpiani Alpiani (PONGGAWA : Journal of Fisheries Socio-Economic, 2026)
Resilience is the ability of a community to adapt, survive, and recover from various challenges and pressures faced, whether from environmental, social, or economic factors. This study aims to identify the forms of resilience and adaptation strategies carried out by the pa'perre-perre fishing community in Maccini Sombala Village, as well as to determine the supporting and inhibiting factors of resilience in the pa'perre-perre fishing community in Maccini Sombala Village. This study was conducted in December 2024-January 2025. This study uses a qualitative descriptive analysis method, and the determination of informants uses a purposive sampling method with data collection through in-depth interviews, observations, and literature studies, and documentation. The results of the study show resilience to modernization through ecological, social, and economic adaptation. Adaptation strategies include adjusting fishing patterns, strengthening community solidarity based on Siri' na Pacce values, and utilizing technology such as GPS and LED lights. This innovation increases the efficiency of anchovy fishing, although fishermen still face challenges such as limited capital and digital literacy.